2022
DOI: 10.1097/md.0000000000029454
|View full text |Cite
|
Sign up to set email alerts
|

Global trends of ERCP research in the last 25 years: A bibliometrics study

Abstract: Endoscopic retrograde cholangiopancreatography (ERCP) has been used in clinical practice for over 50 years. This study aims to investigate the current state of research in the field of ERCP.Methods: Web of Science database was searched using the term "ERCP" for articles published between 1994 and 2018. The total number of articles from the top 20 countries with the most published articles was determined. The top 5 countries were compared in terms of output per capita, number of articles published in top journa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…It provides comprehensive citation index records and primarily focuses on the natural sciences. [ 7 ] Several studies have demonstrated that WOS offers higher accuracy and periodicity compared to databases like Scopus. While Science Direct encompasses a wide range of journals, it has a relatively smaller number and variety of journals compared to the WOS database.…”
Section: Methodsmentioning
confidence: 99%
“…It provides comprehensive citation index records and primarily focuses on the natural sciences. [ 7 ] Several studies have demonstrated that WOS offers higher accuracy and periodicity compared to databases like Scopus. While Science Direct encompasses a wide range of journals, it has a relatively smaller number and variety of journals compared to the WOS database.…”
Section: Methodsmentioning
confidence: 99%
“…We use the database WOSCC [SCI-E] because it covers authoritative, high-impact scholarly journals worldwide, contains comprehensive citation indexing records, and focuses on the natural sciences. [ 24 ] Some studies have shown that WOS has higher accuracy and period than Scopus and other databases. [ 25 ] Although PubMed is the central biomedical search platform, it is a typical abstract-based database and lacks citation information.…”
Section: Methodsmentioning
confidence: 99%
“…The datasets generated during and/or analyzed during the current study are not publicly available, but are available from the corresponding author on reasonable request. Medicine submucosal dissection, [12] endoscopic retrograde cholangiopancreatography, [13] and endoscopic ultrasound [14] were conducted using this method. In order to provide references for future research direction and collaboration, we set out to clearly investigate the beginning and significant turning points of the research on POEM.…”
Section: The Authors Have No Funding and Conflicts Of Interest To Dis...mentioning
confidence: 99%
“…[11] It can be used by researchers to spot trends and pinpoint new areas of study. [11] Related studies such as endoscopic submucosal dissection, [12] endoscopic retrograde cholangiopancreatography, [13] and endoscopic ultrasound [14] were conducted using this method. In order to provide references for future research direction and collaboration, we set out to clearly investigate the beginning and significant turning points of the research on POEM.…”
Section: Introductionmentioning
confidence: 99%